2002
DOI: 10.1021/ol020123j
|View full text |Cite
|
Sign up to set email alerts
|

Palladium−Charcoal-Catalyzed Reduction of Tri-O-acetyl-β-l-Fucopyranosyl Cyanide:  A Route to Small Cluster Oligosaccharide Mimetics (SCOMs)

Abstract: [reaction: see text] Synthesis of glycosyl cyanides was optimized with a new catalyst system. Reduction of tri-O-acetyl-beta-L-fucopyranosyl cyanide with Pd-hydrogen, in the presence of Ac(2)O and Boc(2)O, gave N-protected-mono- and -di-(2,3,4-tri-O-acetyl-beta-L-fucopyranosylmethyl)-amines, which allow for the syntheses of small cluster oligosaccharide mimetics of fucopyranosylomethyl-substituted ureas. From di-(2,3,4-tri-O-acetyl-beta-L-fucopyranosylmethyl) amine was also prepared a carbamoyl chloride as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…When per-O-acetyl-α-or β-D-glucopyranose was treated with excess TMS-CN and 0.1 molar equiv of HgBr 2 in nitromethane for 2 days in the absence of Hg(CN) 2 , the major product was the 1,2-cyanoethylidene derivative 14 in 59% yield, along with only 5% of the preferred cyanide 15, and about 28% of starting material (Scheme 4) [54][55][56], similar to the results of Coxon and Fletcher with Hg(CN) 2 [44]. When we increased the amount of HgBr 2 to at least 0.5 equiv, the cyanoethylidene intermediate rearranged into the desired per-O-β-D-glucopyranosyl cyanide 15 in 51% yield starting from per-Oacetyl-β-D-glucopyranose, or 65% yield from purified cyanoethylidene intermediate 14, within 1 day.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…When per-O-acetyl-α-or β-D-glucopyranose was treated with excess TMS-CN and 0.1 molar equiv of HgBr 2 in nitromethane for 2 days in the absence of Hg(CN) 2 , the major product was the 1,2-cyanoethylidene derivative 14 in 59% yield, along with only 5% of the preferred cyanide 15, and about 28% of starting material (Scheme 4) [54][55][56], similar to the results of Coxon and Fletcher with Hg(CN) 2 [44]. When we increased the amount of HgBr 2 to at least 0.5 equiv, the cyanoethylidene intermediate rearranged into the desired per-O-β-D-glucopyranosyl cyanide 15 in 51% yield starting from per-Oacetyl-β-D-glucopyranose, or 65% yield from purified cyanoethylidene intermediate 14, within 1 day.…”
Section: Methodsmentioning
confidence: 99%
“…The omission of Hg(CN) 2 was crucial. This suggested that rearrangement required the assistance of a mercuric isocyanide complex in conjunction with the existence of equilibrium between the exo-cyanoethylidene 14 and the acetoxonium intermediate [55,56].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations